2010
DOI: 10.1038/ajh.2009.221
|View full text |Cite
|
Sign up to set email alerts
|

Haplotype-Based Case-Control Study on Human Apurinic/Apyrimidinic Endonuclease 1/Redox Effector Factor-1 Gene and Essential Hypertension

Abstract: Based on the present results, the G-T-T haplotype appears to be a genetic marker of EH, and the APE1/REF-1 gene appears to be a susceptibility gene for EH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…8-oxodG is one of the most abundant lesions in oxidatively damaged DNA and was found to induce mutations through G-to-T transversions (7). Oxidatively damaged DNA has been recognized to be associated with the development of some degenerative diseases, essential hypertension (37), and cancer, including kidney tumors (8,21). Nrf2 is able to protect cells from oxidative DNA damage in vivo: Nrf2-deficient, but not wild-type, mice that are exposed to diesel exhaust particles showed increased levels of 8-oxodG in bronchial epithelial cells (1,38), pointing out the importance of Nrf2 in the fight against oxidative DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…8-oxodG is one of the most abundant lesions in oxidatively damaged DNA and was found to induce mutations through G-to-T transversions (7). Oxidatively damaged DNA has been recognized to be associated with the development of some degenerative diseases, essential hypertension (37), and cancer, including kidney tumors (8,21). Nrf2 is able to protect cells from oxidative DNA damage in vivo: Nrf2-deficient, but not wild-type, mice that are exposed to diesel exhaust particles showed increased levels of 8-oxodG in bronchial epithelial cells (1,38), pointing out the importance of Nrf2 in the fight against oxidative DNA damage.…”
Section: Discussionmentioning
confidence: 99%
“…APE1/Ref-1 can modulate susceptibility toward these human diseases via its dysregulation, post-translational modifications or polymorphism in its sequence, as observed by various research groups for several cancer types (for example, ovarian, gastro-esophageal, pancreatico-biliary, lung, prostate, cervical, colorectal, breast, hepatocellular, bladder, head and neck, gastric, and glial cancers). 71, 134 The same is true for diseases such as CVD, 31, 71, 135 AD, 26, 27, 28, 136 Parkinson's disease (PD), 28, 137 Huntington's disease (HD), 138 amyotropic lateral sclerosis (ALS), 139 cerebral ischemia 140 and HIV pathogenesis. 141 These studies underscore the diverse functional association of APE1/Ref-1 with various human diseases, indicating that this is a promising therapeutic research area for the treatment and management of human diseases.…”
Section: Ape1/ref-1 and Human Diseasesmentioning
confidence: 96%
“…31 In an another study, an association between APE1/Ref- 1 gene polymorphism and essential hypertension was observed. 135 A study was carried out using the COS-7 cell line and an APE1/Ref-1 +/− mouse model to study the role of endogenous APE1/Ref-1 in the regulation of endothelium-dependent vascular tone and systemic blood pressure. 71 Damaged endothelium-dependent vascular relaxation due to reduced eNOS activity and basal endothelial NO production was observed in APE1/Ref-1 +/− mice relative to WT mice.…”
Section: Ape1/ref-1 and Human Diseasesmentioning
confidence: 99%
“…Previous studies reported that the rs1760944 genetic variant is associated with cerebral infarction, hypertension, and lung cancer susceptibility. ( 14–17 ) However, no studies have reported on the possible association between the rs1760944 polymorphism and gastric cancer survival. Thus, the aim of the present study is to determine the association between APE1 rs1760944 polymorphism and prognosis in gastric cancer in a Chinese population.…”
mentioning
confidence: 99%